ldcf.net
当前位置:首页 >> 解方程:6x=24 4.5x=90 0.8x=9.6 x÷3=12 y÷2.8=11 ... >>

解方程:6x=24 4.5x=90 0.8x=9.6 x÷3=12 y÷2.8=11 ...

6x=24 x=24÷6 x=4 4.5x=90 x=90÷4.5 x=20 0.8x=9.6 x=9.6÷0.8 x=12 x÷3=12 x=12*3 x=36 y÷2.8=11 y=11*2.8 y=30.8

(1)8×9-6x=18 8×9-6x+6x=18+6x 18+6x=72 18+6x-18=72-18 6x=54 6x÷6=54÷6 x=9;(2)2x÷2.8=8.22x÷2.8×2.8=8.2×2.8 2x=22.96 2x÷2=22.96÷2 x=11.48;(3)4(90-6x)=48 4(90-6x)÷4=48÷4 90-6x=12 90-6x+6x=12+6x 12+6x=90 12+6x-12=90-12 6...

(1)46/x=2.3 x=46/2.3 x=20 (2)6x-0.2=1 6x=1+0.2 6x=1.2 x=1.2/6 x=0.2

2.7x+3=97.5 解:2.7x=97.5-3 x=94.5÷2.7 x=35 0.95÷0.4x=1.9 解:0.4x=0.95÷1.9 x=0.5÷0.4 x=1.25 6.8+x=24.5 解: x=24.5-6.8 x=17.7 6x-4x7.5=24 解: 6x=24+30 x=54÷6 x=9 4.8x-8=25.6 解:4.8x=25.6+8 x=33.6÷4.8 x= 7 12x-6x5=210 解: 12...

✘+4.8=7.2

x2-6x+2=0移项,得x2-6x=-2,即x2-6x+9=-2+9,∴(x-3)2=7,解得x-3=±7,即x=3±7.∴x1=3+7,x2=3-7.

6×0.2+x÷2=11.4 x÷2=11.4-1.2 x÷2×2=10.2×2 x=20.4 2. 4(3x+0.3)=3.2×3 12x+1.2=9.6 12x=9.6-1.2 x=0.7 3 .2÷x-6+8.8=10.8 2÷x=10.8-2.8 2÷x×x=8×x 8x=2 x=0.25 4. 8÷(9x-60-2x)=0.8 8÷(7x-60)=0.8 8÷(7x-60)×(7x-60)=0.8(7x-60) 8=0.56x-48 0.5...

(1)6x-8=40 6x-8+8=40+8 6x=48 6x÷6=48÷6 x=8;(2)2x+5x=10.5 7x=10.5 7x÷7=10.5÷7 x=1.5;(3)4y-2.5×4=15 4y-10=15 4y-10+10=15+10 4y=25 4y÷4=25÷4 y=254.

网站首页 | 网站地图
All rights reserved Powered by www.ldcf.net
copyright ©right 2010-2021。
内容来自网络,如有侵犯请联系客服。zhit325@qq.com